A DYNAMIC SIMULATION OF REVERSE OSMOSIS SYSTEMS - Armijo C., J. (2012)
This paper develops a mathematical model to simulate dynamically a reverse osmosis system. The model is formed from materials balances macroscopic unsteady state combined with the model membrane transport: diffusion-solution. In this first part, we solve the system of differential equations assuming a completely mixed flow pattern in the reverse osmosis module (module polarization = 1). The system of equations is solved simultaneously by the Runge-Kutta-Fehlberg method. The results indicate that increasing the area of membrane or pressure increases the volume of recovered product and increasing the initial concentration in the feed reduces the permeate flow severely.